2022
DOI: 10.1097/mou.0000000000001051
|View full text |Cite
|
Sign up to set email alerts
|

Role of microbiome in kidney stone disease

Abstract: Purpose of reviewThe process of renal stone formation is complex, multifactorial, and variable depending on the type of stone. The microbiome, whether by direct or indirect action, is a factor that both promotes the formation and protects from developing of renal stones. It is a highly variable factor due to the great interindividual and intraindividual variability that it presents. In recent years, with the incorporation of nonculture-based techniques such as the high-throughput sequencing of 16S rRNA bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…[ 78 ], it is now necessary to consider that urinary bacteria are also involved in the formation of calcium oxalate stones, with the exact mechanism yet to be elucidated. The urinary microbiota could act by altering the urine pH, producing metabolites that influence the solubility of minerals in the urine, interacting with substances like citrate that inhibit stone formation, increasing oxalate concentration, or serving as nuclei for mineral crystallization [ 22 , 31 , 64 , 79 , 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 78 ], it is now necessary to consider that urinary bacteria are also involved in the formation of calcium oxalate stones, with the exact mechanism yet to be elucidated. The urinary microbiota could act by altering the urine pH, producing metabolites that influence the solubility of minerals in the urine, interacting with substances like citrate that inhibit stone formation, increasing oxalate concentration, or serving as nuclei for mineral crystallization [ 22 , 31 , 64 , 79 , 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results of a number of recent clinical studies described significant differences in urinary microbiome between stone formers and non-stone formers [ 55 , 73 ]. There was lower diversity of urinary microbiota and differential representation of inflammation associated bacteria in male CaOx stone formers compared to normal controls [ 74 ].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…A variety of reasons can cause kidney and urinary stones. It has been reported that modifiable factors, particularly environmental and dietary ones, are associated with the likelihood of developing kidney stones, including being overweight or obese, the quantity and composition of fluids consumed, the DASH diet a dietary regimen abundant in low-fat dairy products, fruits, and vegetables and the amount of dietary calcium consumed [16] influenced by metabolic, genetic, nutritional, anatomical structure [17,18] as well as family history [19], manual labor employment [20], and socioeconomic profiles [21].…”
Section: Introductionmentioning
confidence: 99%